(untitled) (Global Journal of Science Frontier Research, 2016)
The genus pea is originated in Near Eastern and Mediterranean centers of diversity. Since Ethiopia is one of the Vavilov’s centers of origin of cultivated flora, distribution of the single Pisum sativum subsp. abyssinicum A. Braun is in Ethiopia in the Ancient Mediterranean area of origin of cultivated plants. Field pea is one of the oldest crops in Ethiopia with a unique subspecies developed in Ethiopia, Pisum sativum subsp. abyssinicum. Dekoko (Pisum sativum var, abyssinicum) an important crop in mixed farming and is widely mixed with the main cereal crops growing in south Tigray such as sorghum, barely and teff and is the potential grain growing or cultivated in the region with chick pea, linseed, grass pea and fenugreek. While varieties of field peas can be found around the world. The existing field pea germplasm endemic to Northern part the Ethiopia particularly the highland areas of South Tigray and the Northern part of the former province of Wollo has a phenotypic diversity and tolerance/resistance to disease. Dekoko is capable of producing seed yield of up to 1.95 t/ha under phosphorus fertilization but not yet record data without fertilizer treatment. Dekoko can be used as landrace in Ethiopia because, land races are the genetic wealth that a crop acquires over many years of its existence and have considerable breeding values as they contain valuable adaptive genes to different circumstances.